Toxicological Properties of 7-Methylguanine, and Preliminary Data on its Anticancer Activity - Kirsanov, Kirill; Fetisov, Timur; Antoshina, Elena; Trukhanova, Lubov; Gor’kova, Tatiana; Vlasova, Olga; Khitrovo, Irina; Lesovaya, Ekaterina; Kulbachevskaya, Nataliya; Shcherbakova, Tatiana; Belitsky, Gennady; Yakubovskaya, Marianna; et al. (Frontiers in Pharmacology, 2022)
7-Methylguanine (7-MG) competitively inhibits the DNA repair enzyme poly(ADP-ribose) polymerase (PARP) and RNA-modifying enzyme tRNA-guanine transglycosylase (TGT) and represents a potential anticancer drug candidate. Furthermore, as a natural compound, it could escape the serious side effects characteristic for approved synthetic PARP inhibitors. Here we present a comprehensive study of toxicological and carcinogenic properties of 7-MG. It was demonstrated that 7-MG does not induce mutations or structural chromosomal abnormalities, and has no blastomogenic activity. A treatment regimen with 7-MG has been established in mice (50 mg/kg per os, 3 times per week), exerting no adverse effects or changes in morphology. Preliminary data on the 7-MG anticancer activity obtained on transplantable tumor models support our conclusions that 7-MG can become a promising new component of chemotherapy.